Induced Averaging Aggregation Operators with Interval Pythagorean Trapezoidal Fuzzy Numbers and their Application to Group Decision Making - Shakeel, M.; Rahman, K.; Khan, M.S. A.; Ullah, Murad (The Nucleus, 2017)
Pythagorean fuzzy number is a new tool for uncertainty and vagueness. It is a generalization of fuzzy numbers and intuitionistic fuzzy numbers. This paper deal with induced interval Pythagorean trapezoidal fuzzy numbers. In this paper we introduce induced interval Pythagorean trapezoidal fuzzy numbers and some operation on I-IPTFN, and we also define different types of operators for aggregating induced interval Pythagorean trapezoidal fuzzy numbers. We present induced interval Pythagorean trapezoidal fuzzy ordered weighted averaging (I-IPTFOWA) operator and induced interval Pythagorean trapezoidal fuzzy hybrid averaging (I-IPTFHA) operator. Finally we develop a general algorithm for group decisionmaking problem.